The Art of Sound: Phono-Stylistic Perspectives in Bohemian Rhapsody - Azzahra, Sekar; Ilma, Dzikri; Simanjuntak, Ivan Fernando; Rangkuti, Rahmadsyah (Universitas Pamulang, 2025)
This study examines the phonetic and stylistic elements of